Examining the Moderating Role of Independent Parties in the Effect of Board Diversity on CSR Disclosure in the Context of the Indonesian Capital Market - Lukman, Hendro; ., Haliah; ., Amelia (Journal of Cultural Analysis and Social Change, 2025)
The SRI-KEHATI index serves as a reference for investors interested in companies committed to Sustainable and Responsible Investment (SRI) and Environmental, Social, and Governance (KEHATI) principles. This research aims to analyze the influence of women on the Board of Directors and the age of the board, with a focus on how these factors are moderated by the Audit Committee and Independent Commissioners in relation to Corporate Social Responsibility Disclosure (CSRD) from 2018 to 2022. The study examined a sample of 14 companies and employed Moderated Regression Analysis for the analysis. The findings reveal that the presence of women on the board and the age of the board positively influence CSRD. However, only the age of the board is effectively moderated by the Audit Committee. The implication of these results is that Audit Committees and Independent Commissioners should enhance their understanding of the significance of CSRD information. This understanding can help to reduce information asymmetries between management and stakeholders, ultimately contributing to sustainability.